2006
DOI: 10.1007/s10562-006-0072-4
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of Light Alkanes Over Rhenium Catalysts on Conventional and Mesoporous MFI Supports

Abstract: Recently, Re/HZSM-5 (Si/Al = 15) was shown to be an efficient catalyst for ethane dehydrogenation and aromatization at 823 K and atmospheric pressure. In this reaction, the major initial products were benzene, toluene and xylene (BTX), but increasing amounts of ethene were produced with time on stream due to deactivation of the catalyst. We show that by use of rhenium impregnated MFI supports with very few or no acidic sites (Si/Al > 500), highly selective ethane dehydrogenation catalysts are obtained with eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…[13,14] In order to directly convert alkanes to aromatics, a bifunctional catalyst is required, which in addition to the acid function comprises the dehydrogenation functionality of metal such as Ga, Zn, Mo, Re or Pt. [15][16][17][18][19][20][21][22][23] Numerous studies demonstrated that incorporation of Lewis acid metals such as Zn into zeolites modifies the surface acidity and enhances selectivity to BTX in light alkane dehydroaromatization. [7,15,18,[24][25][26][27] However, only a few studies have been dedicated to the performance and catalytic life-time enhancement of Zn-containing zeolite catalyst for ethane direct conversion to aromatics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13,14] In order to directly convert alkanes to aromatics, a bifunctional catalyst is required, which in addition to the acid function comprises the dehydrogenation functionality of metal such as Ga, Zn, Mo, Re or Pt. [15][16][17][18][19][20][21][22][23] Numerous studies demonstrated that incorporation of Lewis acid metals such as Zn into zeolites modifies the surface acidity and enhances selectivity to BTX in light alkane dehydroaromatization. [7,15,18,[24][25][26][27] However, only a few studies have been dedicated to the performance and catalytic life-time enhancement of Zn-containing zeolite catalyst for ethane direct conversion to aromatics.…”
Section: Introductionmentioning
confidence: 99%
“…In order to directly convert alkanes to aromatics, a bi‐functional catalyst is required, which in addition to the acid function comprises the dehydrogenation functionality of metal such as Ga, Zn, Mo, Re or Pt . Numerous studies demonstrated that incorporation of Lewis acid metals such as Zn into zeolites modifies the surface acidity and enhances selectivity to BTX in light alkane dehydroaromatization .…”
Section: Introductionmentioning
confidence: 99%
“…were employed as catalyst supports. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Miller et al prepared a Pt-In intermetallic alloy and found that the Pt 3 In phase exhibited a superior ethane turnover rate (TOR) of 5.3 s −1 and 99% ethylene selectivity at 600 °C, and this catalyst exhibited little deactivation in 5 h. Compared with a monometallic Pt catalyst, the electronic changes and geometric changes were responsible for the higher TOR and ethylene selectivity of the PtIn alloy. 1 Wang et al deposited Pt and Sn over hydrotalcite materials (MgGaAlO) and found that the presence of Ga enhanced the interaction of the Sn-support and Pt-Sn, maintaining the oxidized Sn species and improving the EDH activity.…”
Section: Introductionmentioning
confidence: 99%
“…In order to form stable Pt-based NDE catalysts, the support should be thermally stable, have a sufficiently high specific surface area, be free of Brønsted acidity for hosting undesirable side reactions, and have Lewis acidity and amphoteric silanol (−OH) groups to contribute to optimum metal dispersion. , In search of a suitable support material, metal oxides such as alumina (Al 2 O 3 ) or aluminate (e.g., MgAl 2 O 4 ) have been used for Pt-based catalysts. ,, Zeolite-based materials are ideal alternatives to metal oxide supports due to their high surface area, uniform micropores, and tunable acidity by adding alkaline cations and/or isomorphous substitution of Lewis acidity centers. For example, the aluminosilicate zeolite with an MFI (Mobil-type five) framework structure (i.e., ZSM-5, Zeolite Socony Mobil-5) has been used as the support for rhenium (Re), molybdenum (Mo), and iron (Fe) species for NDE reactions, in which metal species were loaded by the wetness impregnation approach. In order to enhance metal dispersion and modulate zeolite acidity, the heteroatom (i.e., Fe and gallium (Ga))-isomorphously substituted ZSM-5 zeolites were reported.…”
Section: Introductionmentioning
confidence: 99%